The prospective relationship of sport and physical activity with life satisfaction after a one-year follow-up: an examination of gender differences during mid-adolescence - Gomez-Baya, Diego; Mendoza, R., R.; Tomico, A. (Cuadernos de Psicología del Deporte, 2018)
Physical and sport activity has been associated not only to better physical health during adolescence, but also to better mental health. Life satisfaction plays an important role in facilitating social relationships and preventing the development of psychological disorders during adolescence. This study aimed to analyse by gender the effect sport participation and the practice of physical exercise, as extracurricular activities, on life satisfaction during adolescence. A longitudinal study with two assessments separated by a year was carried out. A self-report measure was administered in each wave to a sample of 714 adolescents (50.7% girls) aged between 13 and 16 years old. Participants were enrolled in a convenience selection of 19 Secondary schools from Andalusia (Spain), while the classrooms were randomly selected. Results indicated that boys reported more frequent sport practice and physical activity than girls. A structural equation model indicated that a higher frequency of physical activity and a higher frequency of sport activity, as extracurricular activities, longitudinally predicted a greater life satisfaction in adolescent girls after the one-year follow-up, whilst no significant association was detected in boys' subsample. These results highlight the need to design gender-focused actions to promote the practice of physical and sport activity in order to foster adolescent well-being.